Feasibility and safety of CD19 chimeric antigen receptor T cell treatment for B cell lymphoma relapse after allogeneic hematopoietic stem cell transplantation - Schubert, Maria-Luisa; Dietrich, Sascha; Schmitt, Anita; Kunz, Alexander; Bondong, Andrea; Stadtherr, Peter; Ho, Anthony Dick; Müller-Tidow, Carsten; Schmitt, Michael; Dreger, Peter (Biology of blood and marrow transplantation, 2020)
Although CD19-directed chimeric antigen receptor (CAR) T cells have been successfully used after a preceding allogeneic stem cell transplant (alloHCT) in patients with acute lymphoblastic leukemia, little is known about the feasibility and outcome of CAR T cell treatment in patients who have been previously allotransplanted for lymphoma. In a single-center retrospective analysis, course and outcome of all allografted patients treated with CD19 CAR constructs for B cell lymphoma between October 2018 and November 2019 were studied. CAR therapy consisted either of a third-generation CAR (HD-CAR-1) or of commercially manufactured axicabtagene ciloleucel (axi-cel; Gilead, Santa Monica, U.S.). Altogether, 10 CAR T cell dosings using recipient leukapheresis products were performed in 8 patients: 4 patients (2 mantle cell lymphoma, 2 chronic lymphocytic leukemia) received 6 dosings with HD-CAR-1 and 4 patients (all with diffuse large B cell lymphoma) received 4 dosings with axi-cel. Overall, 6 of 8 patients (75%) responded. CAR treatment was well tolerated with grade ≥ 3 cytokine release syndrome and neurotoxicity each being observed after 1 of 10 dosings. A single patient had moderate chronic graft-versus-host disease. Of note, 3 of 4 patients who received axi-cel had ongoing grade ≥ 3 cytopenia 3 months postdosing, whereas prolonged cytopenia was not observed in 9 alloHCT-naive patients who received axi-cel during the same time period. In conclusion, CAR T cell treatment from recipient-derived leukapheresis products after a prior alloHCT appears to be feasible, effective, and safe in patients with B cell lymphoma. Protracted cytopenia after axi-cel treatment is a matter of concern and requires further exploration.